March for Our Lives Movement Strategy for Gun Control Law Reformation of America in 2018-2019 - Alizarzady, Muhammad Asief; Khurun'in, Irza (Sociology Department Of Syiah Kuala University, 2023)
Gun violence appears to be widespread in American culture. The year 2018 became a momentum for the founders and activists of the March For Our Lives movement, specifically the Stoneman Douglas High School Mass Shooting. This Movement's accomplishments are quite remarkable; the most important thing is that they were able to pass around 60 bills on safer firearms. The purpose of this research is to analyze the advocacy strategies employed by the March For Our Lives Movement. One of their efforts to carry out advocacy activities is the formation of the Transnational Advocacy Network (TAN). The network then employs a variety of strategies, including Information Politics, Symbolic Politics, Leverage Politics, and Accountability Politics. This research employs a qualitative method with a descriptive approach. The literature study was used to collect data from secondary sources.